Analysis of Factors Affecting the Effectiveness of Sugarcane Marketing System among Farmers Supplying Ngadiredjo Sugar Factory in Ponggok District, Blitar Regency - Septian Maulana Purnama; Fadli Mulyadi; xenia putri purbaningrum; Bayu Ardika Nur Ramadhan (JURNAL AGRIMENT, 2026)
The sugarcane marketing system plays an important role in improving farmers' welfare and ensuring the sustainability of sugar production in Indonesia. This study aims to analyze the effect of sugarcane prices received by farmers, marketing costs, and partnerships with sugar factories on the effectiveness of the sugarcane marketing system in Ponggok District, Blitar Regency. This research used a quantitative method with a survey approach. Data were collected through questionnaires distributed to 66 sugarcane farmers. The data analysis technique used multiple linear regression analysis with validity, reliability, and classical assumption tests including normality, multicollinearity, and heteroscedasticity tests. The results showed that the sugarcane price variable had a positive and significant effect on the effectiveness of the marketing system, the marketing cost variable had a positive but insignificant effect, and the partnership variable had a positive and significant effect. Simultaneously, all independent variables significantly affected the effectiveness of the sugarcane marketing system. The coefficient of determination value of 52.06% indicated that the effectiveness of the sugarcane marketing system could be explained by the variables studied, while the rest was influenced by other factors outside the model.